Russia's role in the war in Donbass, and the threat to European security. Issue 4 (1st October 2016) - Robinson, Paul
ABSTRACT: The Russian annexation of Crimea, and the subsequent war in Donbass, have led to a great deal of speculation about Russia's objectives and their implications for European security. This article examines Russian intentions by means of an analysis both of official rhetoric and of Russia's actions in Donbass. It concludes that far from instigating the rebellion in Donbass and using it to destabilise Ukraine, revise the international order, or seize additional territory, Moscow has largely been reacting to events and trying to gain some control of a process which was originally almost entirely outside of its control. Its primary aim has been to get the Ukrainian government to negotiate directly with the rebels, in order to produce a permanent peace settlement based upon some form of special status for Donbass within Ukraine. It has also used its influence over the rebels in order to persuade them to cooperate with the peace process set up at Minsk. Russia's objectives are very limited, and do not pose a serious threat to European security as a whole.